Analyzing Animal Welfare Policies in Sustainable Strategies of the Luxury Industry - Gong, Ran (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of the global economy and the significant improvement in people's quality of life, society has higher and higher expectations for enterprises' sustainable development performance. The current research on sustainable development strategies in the luxury industry is extensive, but rarely incorporates animal welfare policies. This paper aims to address this research gap by using Hermès as an example. It explores the company's animal welfare strategies implemented under the framework of sustainable development, analyzes how it has enhanced its brand image, strengthened consumer loyalty, and established a benchmark in the industry through its high standards of animal welfare measures, which are supported by science, data, and practical experience. It is setting a benchmark for the industry. At the same time, this paper also puts forward prospective suggestions for further optimizing Hermès' sustainable development strategy, intending to fill the gaps in the research on animal welfare policies of luxury brands, enrich the theoretical framework of sustainability research on luxury brands, and provide practical experiences for brands inside and outside the industry to jointly promote the sustainable development of the whole industry.